2022
DOI: 10.1111/jonm.13778
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, resilience and psychological flexibility in frontline nurses during the acute phase of the COVID‐19 pandemic (2020) in Madrid, Spain

Abstract: Background In April 2020, Spain was the country with the highest number of patients infected by COVID‐19 in Europe. The pressure on health care providers has had a direct impact on nurses and their mental health. Aim The aim of this study is to demonstrate the causal relationship between resilience, acceptance, experiential avoidance, psychological inflexibility and burnout syndrome, all of which are measured with validated questionnaires. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The results of the current study indicated that higher levels of resilience were associated with lower levels of emotional exhaustion, depersonalization, and diminished personal accomplishment among nurses working in Thailand during the pandemic period. The findings largely confirm previous studies where higher resilience has been linked to lower emotional exhaustion, depersonalization, and reduced personal accomplishment among nurses working in public hospitals in Madrid, Spain [ 20 ], nurse managers in tertiary public hospitals in China [ 25 ], nurses and nursing students from a college and a state nursing association in Pennsylvania, USA [ 18 ], nurses in Brazil [ 42 ], and hospital staff in Australia [ 4 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of the current study indicated that higher levels of resilience were associated with lower levels of emotional exhaustion, depersonalization, and diminished personal accomplishment among nurses working in Thailand during the pandemic period. The findings largely confirm previous studies where higher resilience has been linked to lower emotional exhaustion, depersonalization, and reduced personal accomplishment among nurses working in public hospitals in Madrid, Spain [ 20 ], nurse managers in tertiary public hospitals in China [ 25 ], nurses and nursing students from a college and a state nursing association in Pennsylvania, USA [ 18 ], nurses in Brazil [ 42 ], and hospital staff in Australia [ 4 ].…”
Section: Discussionsupporting
confidence: 88%
“…An individual demonstrating resilience actively endeavors to progress constructively, drawing upon the insights and knowledge gained from confronting adverse experiences. Indeed, several studies among healthcare workers and nurses during the pandemic have found associations between resilience and lower levels of burnout [ 4 , 20 , 25 , 42 ], intention to leave [ 29 , 40 ] and a higher level of work engagement [ 9 , 26 ]. However, these studies have been limited to the United States, Australia, China, Brazil, and Spain.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that the number of days spent directly providing care to patients with COVID-19 infections was significantly correlated with feelings of DP among nurses (Jiménez-Fernández et al, 2022 ). While the frontline nurses in our study tended to express symptoms of DP more than the nonfrontline workers, there were no significant differences in the 3 burnout scores of physicians who worked on the front line and those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…The Insomnia Severity Index (ISI) is a 7-item self-report questionnaire assessing the nature, severity, and impact of insomnia via a 5-point Likert scale during the "last month", yielding a total score ranging from 0 to 28 [47]. The total score was interpreted as follows: absence of insomnia (0-7); sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14); moderate insomnia (15)(16)(17)(18)(19)(20)(21); and severe insomnia (22)(23)(24)(25)(26)(27)(28). The dimensions evaluated were severity of sleep onset, sleep maintenance, early morning awakening problems, sleep dissatisfaction, interference of sleep difficulties with daytime functioning, noticeability of sleep problems by others, and distress caused by sleep difficulties.…”
Section: Outcome Measuresmentioning
confidence: 99%